Downregulation of the Mitochondrial Calcium Uniporter by Cancer-Related miR-25 - Marchi, Saverio (Cell Press, 2013)
The recently discovered mitochondrial calcium uniporter (MCU) promotes Ca(2+) accumulation into the mitochondrial matrix [1, 2]. We identified in silico miR-25 as a cancer-related MCU-targeting microRNA family and demonstrate that its overexpression in HeLa cells drastically reduces MCU levels and mitochondrial Ca(2+) uptake, while leaving other mitochondrial parameters and cytosolic Ca(2+) signals unaffected. In human colon cancers and cancer-derived cells, miR-25 is overexpressed and MCU accordingly silenced. miR-25-dependent reduction of mitochondrial Ca(2+) uptake correlates with resistance to apoptotic challenges and can be reversed by anti-miR-25 overexpression. Overall, the data demonstrate that microRNA targeting of mitochondrial Ca(2+) signaling favors cancer cell survival, thus providing mechanistic insight into the role of mitochondria in tumorigenesis and identifying a novel therapeutic target in neoplasia.